Deixis Found in The Utterances by The Main Character of “Enola Holmes” Movie - Yesika Cindhe Puspa; I Gusti Ayu Vina Widiadnya Putri; Ni Made Verayanti Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This research focuses on the types of deixis used in Enola Holmes movie by Harry Bradbeer. The aim of this research is to identify the type of deictic words used by the main character in the Enola Holmes film. The data in this study was analysed using a qualitative method, and the data were collected using a library research approach. The data were obtained from Enola Holmes movie according to the theory from Levinson (1983) from his book entitled pragmatics. In this study, 518 deixis data were identified in this film, including person deixis, time deixis, place deixis, discourse deixis, and social deixis. It was found that person deixis are "I, Me, My" which refers to the speaker. For time deixis are “Soon, When I Was a Child” which encode temporal points. For place deixis is “here” encode specific location. For discourse deixis is “that” to indicate some words spoken before and the last is for social deixis “Mr., Mother” to show social distance between the speaker and addressee. The person deixis was shown to be the most dominant types based on the findings. It refers to the function of person deixis, which is directly associated with social interaction.